Osteopenia prevalence in ankylosing spondylitis and its correction with alphacalcidol - B. V. Zavodovsky; L A Zborovsky; N D Chadadze; A B Zborovsky (Научно-практическая ревматология)
Objective. To study osteoporosis (OP) and osteopenia prevalence in ankylosing spondylitis (AS) by ultrasonographic densitometry of heel bone. Results. Examination of 84 pts showed decrease of bone mineral density in 47,62%. OP and osteopenia were more frequent in pts with high activity and advanced radiological stage of the disease, prominent articular syndrome, visceral pathology, longer disease duration, low body mass index, oral glucocorticoid treatment. In pts with OP and osteopenia markers of osteogenesis (osteocalcin total alkaline phosphatase) were in normal limits but osteoresorption indices (cross-laps, urine calcium) were increased. Treatment with alphacalcidol provided significant improvement of bone mineral density, decrease of bone pain and increase of muscular power. Pts of control group receiving calcium 1000 mg/day as monotherapy showed OP progression. Conclusion. Alphacalcidol 0,5-1,0 mg/day can be considered as drug of choice for the treatment of OP and osteopenia in pts with AS.